“The key that no one has asked for”: Elicura Chihuailaf, Poetry, Ritual and Memory (ALPHA. Journal of Arts, Literature and Philosophy, 2002)
Elicura Chihuailaf Nahuelpan, born in Quechurewe, Araucanía region, Chile, in 1952; Obstetrician by profession, university professor and general secretary of the group of indigenous writers, he is part ―along with Jaime Huenún, Bernardo Colipán, Leonel Lienlaf and others― of a notable group of Mapuche poets who since the last decade have forced (he is a that is, of course) to academic criticism and the Chilean reader to discover, just as Columbus, (that is, to see how something that had always been there was unusually new) is an important sector of national literary creation that until then had been practically unknown or simply denied (note)